Employing Image Variation in the Study of Visual Language and Conventional Art Creation: A Detailed Analysis - Tan, Xiujiang; Tan, Long (Transactions on Social Science, Education and Humanities Research, 2023)
Image Variation is an important method to change the traditional way of art creation and visual language research, which emphasises the diversity of creative thinking and expressive vision. Image Variation is a method of artistic creation that aims to challenge traditional concepts of artistic innovation and expression. It emphasises the expansion and alteration of traditional visual language through changes in form, structure and subject matter. Figurative Replacement encourages artists to break through traditional creative methods, including traditional painting, sculpture, photography and other creative ideas. Artists can create new and surprising works by being creative in different ways, introducing digital technologies, using very standardised materials, or changing the constraints of the creative process. This approach helps to break conventional modes of thinking, stimulate innovation and enrich artistic creation. Traditional verbal visuals include a range of signs, symbols, structural diagrams and expressions that are seen as the artist's means of conveying information and emotions. Redefining the visual language by introducing new visual elements, deconstructing traditional elements or reorganising symbols provides the artist with greater freedom. This redefined vision broadens the boundaries of art and also stimulates different ways of interpretation and understanding of the work by the viewer.